1971
DOI: 10.1136/thx.26.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biological fate of polyurethane aortic prostheses

Abstract: A study was carried out to investigate the biological fate of spongy polyurethane aortic prostheses after a period of implantation of 7 to 10 years in dogs. The present findings indicate that this material is in a sense accepted by the organism (not only tolerated) because almost complete reorganization of the arterial elastic structures inside the prostheses and the formation of arterial branches from the prostheses were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…(47) In 1971, Marinescu et al found that when dogs lived years with polyurethane prosthetics, the graft degraded, and a neovessel formed. (48) This then-unseen result spawned ten years of research into polyurethane grafts. (49–54) However, further study found the grafts were not degrading, but eroding.…”
Section: Designs and Progressmentioning
confidence: 99%
“…(47) In 1971, Marinescu et al found that when dogs lived years with polyurethane prosthetics, the graft degraded, and a neovessel formed. (48) This then-unseen result spawned ten years of research into polyurethane grafts. (49–54) However, further study found the grafts were not degrading, but eroding.…”
Section: Designs and Progressmentioning
confidence: 99%
“…The use of polyurethanes in medical devices continues to increase, due to their high-quality physical properties and excellent bio-and hemocompatibility. [1][2][3][4][5] Water-dispersible drug-polyurethane systems can be obtained by means of bonding of the drug to polymer matrix. [6][7][8] Recently, there has been an increasing interest in producing nanoscale fibers by employing electrospinning technology for obtaining biocide materials.…”
Section: Introductionmentioning
confidence: 99%